PELATIHAN PENULISAN ARAB PEGON DAN KALIGRAFI PADA SISWA SEKOLAH MENENGAH ATAS (SMA/MA/SMK) SE-KOTA METRO - Agus Setiawan; Dian Risky Amalia; Muhammad Zaini; Leli Fertiliana Dea; Ahmad Mukhlisin; Nurul Aisyah (Pusat Penelitian dan Pengabdian Kepada Masyarakat (P2M) IKIP Budi Utomo Malang, 2020)
Preserving the culture of the archipelago's Islamic treasures is something that must be done One of the Islamic treasures that needs to be preserved is Penegusan Arabic Calligraphy. To this, community service activities wre carried out to provide training on all Metro City. The method used in mentoring to the community is Appeciative inquiry. The steps were iscovery, dream, design, define and destiny. This service used the Assed-Based Community Development (ABCD) approach. ABCD was ne of the discussions used in community service prioritizing existing assets and potential in the community compared to High School students. The community service activity was carried out in 3 sessions, namely introducing and returning Arabic pegon, training to get calligraphy by the speaker and fixing it with independent calligraphy. The results of this dedication show that tudents who were ble to write Arabic pegon that simultaneously could make alligraphy based on Arabic pegon